A Novel, Portable MESH Nebulizer—An Alternative to Metered Dose Inhaler: Efficacy and Usability in Preschool Wheezers - Ullmann, Nicola; Di Marco, Antonio; Columbu, Fabiana; Negro, Valentina; Chiarini Testa, Maria Beatrice; Panetta, Valentina; Tripodi, Salvatore; Potapova, Ekaterina; Allegorico, Annalisa; Matricardi, Paolo Maria; Cutrera, Renato (Frontiers in Pediatrics, 2020)
Introduction and Objectives: Wheezing episodes are the first causes of doctor’s consultation in pre-school age. Treatment is usually administered with a MDI spacer. At variance, many parents and doctors prefer to use a compressor nebulizer which cannot be easily carried. The study is aimed at testing whether a pocket Mesh nebulizer has similar efficacy and acceptability than a standard MDI device. Materials and Methods: The IPAC study was a randomized, controlled, non-inferiority trial (number: 1616/2018, Ospedale Pediatrico Bambino Gesu' – IRCCS). The study had two arms: cases, using MicroAIR U100, and controls, using MDI+spacer device. Both devices were adopted for long term treatment and for exacerbations. Follow up was organized with clinical visits and a daily e-diary connected to an application for mobile phone. Results: 105 patients were enrolled. The frequency of asthmatic symptoms showed a non-inferiority for MicroAIR U100 group versus MDI. Accordingly, no significant difference was found in the average % of days with cough, wheezing, breathlessness after exercise, days lost at school and not-programmed visits. Considering only patients with >1 day with symptoms, no significant differences were found in the number of exacerbations nor in the cumulative days with symptoms. The acceptance and usability of both devices has been favourable. However, MDI+AeroChamber® device showed better acceptability. Conclusions: Our study shows that MicroAIR U-100, a MESH nebulizer, has similar clinical efficacy but lower acceptance and usability than an MDI plus Aerochamber® in delivering therapy in preschool wheezers. Therefore, MicroAIR U-100 might be a valuable second choice, when the delivery of medication with an MDI plus Aerochamber® is not accepted, or wrongly used by the parents.